An Analytical Study on the Local Electronic Density of States of the Valence Bands in Amorphous Silicon Carbide - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
A formulation for the energy-averaged local valence band density of states of amorphous silicon carbide is derived. To this end, sp3-type hybrid orbitals are employed.